Netnography of video streaming users (National Administration Journal, 2025)
This netnographic study analyzes 495 social media comments about video streaming platforms STAR, Netflix, Amazon, and MAX, identifying user perceptions and behaviors. It highlights expectations, levels of (dis)satisfaction, and information demands. Users value the content and tend to share more information than they request. Satisfaction is associated with positive experiences, while dissatisfaction is linked to technical failures and delays. The analysis provides insights for improving the company–consumer relationship and optimizing services.
Keywords: Marketing; netnography; co-creation; streaming; users